The Effect of a Six-Week Intervention Using Small-Sided Games (SSG), Ladder Drill, and Dynamic Balance on Agility of Young Futsal Players - Ilham, Ilham; Putra, Raffiandy Alsyifa; Orhan, Bekir Erhan; Nusri, Ardi; Zulaini, Zulaini; Kurniawan, Randi; Ayubi, Novadri; Geantă, Vlad Adrian (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to compare the effects of small-sided games (SSG) and ladder drills (LD) on agility performance in futsal players with different levels of dynamic balance (DB), which was examined as a moderating variable. Materials and Methods. Twenty-four male futsal athletes (mean age: 17.1 ± 0.8 years) were randomly assigned to either SSG or LD training groups and further classified into high or low DB levels, forming four experimental subgroups. Over a 6-week intervention (3 sessions/week), participants underwent agility-specific training, and agility was assessed using the Illinois Agility Test. Dynamic balance was measured via the Y Balance Test. A two-way ANOVA with Tukey’s post hoc test (p < 0.05) was used to assess main and interaction effects. Results. Both training interventions produced significant improvements in agility (p < 0.05). Players with high DB showed the most substantial gains following SSG (21.5% improvement), whereas those with low DB benefited more from LD training (11.0% improvement). A significant interaction was observed between training type and DB level, suggesting that agility adaptations depend on athletes’ balance proficiency. Conclusions. The effectiveness of agility training in futsal players is moderated by individual dynamic balance capacity. SSG is particularly beneficial for players with high DB due to its game-representative movement demands, while LD training provides structured improvements for players with low DB. These findings support the implementation of personalised training strategies based on neuromuscular profiles to optimise agility development in futsal.